Association of the Total Cholesterol Content of Erythrocyte Membranes with the Severity of Disease in Stable Coronary Artery Disease. (20th October 2014) - Namazi, Gholamreza; Pourfarzam, Morteza; Jamshidi Rad, Sabieh; Movahedian Attar, Ahmad; Sarrafzadegan, Nizal; Sadeghi, Masoumeh; Asa, Parastoo
Abstract : Increasing evidence suggests that erythrocytes may participate in atherogenesis. We sought to investigate whether the total cholesterol content of erythrocyte membranes (CEM) is significantly different in patients with stable coronary artery disease (CAD) compared to patients with nonsignificant coronary stenosis and determine the correlation between CEM and the severity of coronary stenosis. Methods . The population included 144 patients, undergoing clinically indicated coronary angiography. The severity of coronary stenosis was scored after coronary angiography and patients were divided into two groups; theS -stenosis group (CAD patients, n = 82 ) had a significant stenosis indicated by coronary angiography and the second group, N -stenosis (n = 62 ), had nonsignificant coronary stenosis. Lipid parameters were determined by routine laboratory methods. CEM was measured using an enzymatic assay, and protein content was assessed by the modified Lowry method. Results. The mean of CEM levels was higher (P < 0.001 ) in stable CAD patients (137.2  µ g/mg of membrane protein) compared withN -stenosis patients (110.0  µ g/mg of membrane protein). The coronary artery scores were correlated positively with CEM levels (r = 0.296, P < 0.001 ). Conclusion . CEM levels are positively associated with the severity of CAD, meaning that CEM might contribute to the development of CAD.